The role of JAK/STAT/SOCS3 signaling in rats with brain damage induced by early alcohol exposure after birth - Chen Yang; Jianxiong Gui; Dishue Huang; Ran Ding; Jie Liu; Wenjie Zhao; Jing Yang; Ziyao Han; Lingling Xie; Xiaoyue Yang; Yanan Pan; Mingdan Xie; et al. (Wiley, 2024)
Abstract Early postnatal alcohol exposure can have negative impacts on neonatal rat brain development and function. Our research explored the impacts of alcohol exposure from postnatal day 4 to PD9 on Sprague‒Dawley rat pups. Pups were intragastrically administered with either an alcohol milk solution or a pure milk solution twice daily. On PD10, brains were analyzed via histological and biochemical methods. Alcohol exposure led to growth impairment, behavioral abnormalities, and cognitive deficits. It also reduced microglial numbers in the hippocampus while activating the remaining microglia to secrete IL‐6. In addition, alcohol induced the upregulation of pro‐apoptotic factors and downregulation of the anti‐apoptotic protein BCL‐2 in the hippocampus by activating the JAK/STAT/SOCS3 signaling pathway. Similar effects were observed in vitro when BV‐2 cells were exposed to ethanol and HT‐22 cells were exposed to IL‐6. The drug AG490, a STAT3 inhibitor, mitigated IL‐6‐induced JAK/STAT activation and neuronal apoptosis in HT‐22 cells. Overall, these findings demonstrate that early‐life alcohol exposure triggers an inflammatory microglial response involving the release of IL‐6, which activates JAK/STAT signaling, leading to hippocampal neuronal apoptosis and developmental/cognitive impairments. AG490 may disrupt this inflammatory signaling cascade and cause neuronal damage.